Factors associated with health-related quality of life in overweight schoolchildren in the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: To evaluate factors associated with Health-Related Quality of Life in adolescent schoolchildren during the COVID-19 pandemic. Method: Cross-sectional study, carried out with 87 adolescents from a municipal school in a city in the Midwest of Minas Gerais. The KIDSCREEN 52 scale was used to assess the Health-Related Quality of Life. Self-reported weight and height, socioeconomic level, food consumption and physical activity level were obtained. Multiple linear regression was performed. Data were analyzed using the statistical program Statistical Package for Social Sciences version 21.0. Results: The prevalence of overweight was 32.2% and 56.9% of the adolescents consumed three to five types of processed and/or ultra-processed foods the day before the interview. A percentage of 17.2% of the participants were classified as sedentary and insufficiently active, and participants from social class C 1 had higher medians in the body self-perception domain. Higher medians of the emotional state domain were found in female adolescents and those who consumed processed and ultra-processed foods. Boys had higher medians in the health and physical activity, feelings and friends, and social support domains. The multivariate analysis showed that increasing age and body mass index (BMI) were associated with a decrease in quality of life related to global health. Conclusion: The results show the importance of improving public policies aimed at the quality of life of adolescents with a focus on promoting healthy eating and encouraging physical activity, especially during the COVID-19 pandemic.